The Phenomenon of Da’wa Humor Kiai Pesantren: Sociolinguistic Analysis - Abdullah, Asep Abbas (International Conference of Moslem Society, 2018)
This paper aims to know the model of da'wa done by kiai, and about da'wah has been discussed by (Ahmad Anas: 2006; Atmawati Dwi: 2009; and Anshori Anhar: 1984). While about humor has been discussed by (Muhammad Rohmadi: 2009; Wuri Soedjatmiko: 1991; I Dewa Putu Wijana: 2004; Danandjaja: 2001). Everything has a meaning so that humor is not a goal, but just a medium. For that purpose, the authors use a sociolinguistic perspective, as has been discussed by (Roger T. Bell: 1995; Ralp Fashold: 1990; J. A. Fishman: 1972). Therefore, what is done by Kiai Latif in his dakwah using various humorous models, such as anecdotes, comparisons, plesetan and others (Victor Raskin: 1944, James Danandjaja: 1986). Certainly, what is done by Kiai Latif in his da'wah that uses the language of dakwah humor still in the corridor of da'wah, that is as a means to invite people to not be dissolved in things that are not pleaded by Allah SWT, including inconsistent with the teachings applied by Prophet Muhammad SAW (Andy Darmawan: 2002; Clifford Geertz: 1981; Jakfar Puteh Saifullah: 2006; Aminah Mochtar: 2000).